Investigating the relationship between autistic traits and symptoms and Catatonia Spectrum. Issue 1 (4th November 2022) - Dell'Osso, L.; Amatori, G.; Massimetti, G.; Nardi, B.; Gravina, D.; Benedetti, F.; Bonelli, C.; Luciano, M.; Berardelli, I.; Brondino, N.; De Gregorio, M.; Deste, G.; et al.
Abstract: Background: In recent years, numerous studies have highlighted the overlap between autism spectrum disorder (ASD) and catatonia, both from a clinical and pathophysiological perspective. This study aimed to investigate the relationship between the autism spectrum (autistic traits and ASD signs, symptoms, and behavioral manifestation) and Catatonia Spectrum (CS). Methods: A total sample of 376 subjects was distributed in four diagnostic groups. Subjects were assessed with the Structured Clinical Interview for DSM-5, Research Version, the Adult Autism Subthreshold Spectrum (AdAS Spectrum), and CS. In the statistical analyses, the total sample was also divided into three groups according to the degree of autism severity, based on the AdAS Spectrum total score. Results: A statistically significant positive correlation was found between AdAS Spectrum and CS total score within the total sample, the gender subgroups, and the diagnostic categories. The AdAS Spectrum domains found to be significantly and strongly correlated with the total CS score were hyper–hypo reactivity to sensory input, verbal communication, nonverbal communication, restricted interests and rumination, and inflexibility and adherence to routine. The three groups of different autistic severity were found to be distributed across all diagnostic groups and the CS score increased significantly from the group without autistic traits to the group with ASD. Conclusions: Our study reports a strong correlation between autism spectrum and CS.